Submarine vortices derived from natural gas hydrate conversion: a mechanism for ocean mixing - BARNARD, A.; MAX, M. D.; GUALDESI, L. (Mediterranean Marine Science, 2017)
We propose that the source water for some abyssal undular vortices cored by cool, low-salinity water identified at depths in excess of 2,500 m in the deepwater region of the Eastern Mediterranean Basin may be related to conversion of natural gas hydrate (NGH) in abyssal marine sediments. The conditions for extensive formation of NGH in the gas hydrate stability zones (GHSZ) of the upper seafloor sediments existed in this region during previous glacial episodes when colder water supported a thicker GHSZ. Seafloor warming during the most recent interglacial caused thinning of the GHSZ at its base and has driven endothermic NGH dissociation that would have released large volumes of low-salinity water and gas that would tend to pond below the base GHSZ. Periodically, trapped low-salinity water and gas would be released into the sea through the overlying sediments. Buoyant low-salinity water masses, supersaturated with gas and locally containing free gas would ascend and introduce a dynamic element into an otherwise generally static environment. As a result of the interaction of the rise of this buoyant plume and Coriolis acceleration the ascending mass would begin to rotate and form a vortex tube in midwater. NGH conversion within the seafloor introduces large coherent masses of low-salinity, lower-temperature water containing a buoyant free gas fraction from near-surface reservoirs into the abyssal depths even where there may only be a weak natural gas petroleum system.